PENGARUH KEPEMIMPINAN DAN BUDAYA KERJA TERHADAP MOTIVASI BERDAMPAK KINERJA (Studi Pada Dosen di Kopertis Wilayah VI Kota Semarang) - Sabtarini Kusumaningsih (Universitas PGRI Semarang, 2016)
The position oflecturerin educationisacentralfront guardandthe implementation ofthe learning process, it isnecessaryrelated tothetotality offaculty performance, dedication, andloyaltyasan educatorandprintingsupplies, provisionof Human Resources(HR). Related to this problem, themotivationlecturers is requiredtodevelopquality human resources. Implementation offacultymotivationin doing thetasks assignedto him/her, becausethe success of thelearning objectiveswilldependonhisabilityandsincerity. Researchcarried outquantitatively. The selection ofsamples is usingproportionalrandom samplingtechniqueas many as 100lecturersin theregionKopertisVIof Semarang. Analysis techniquesuseregression. The results showedthat there wasa positiveandsignificant ifluence betweenleadershipvariables(X1) toWork Motivation(Y1) witht-count resultsare9.454and1.985fort-table with a significance valueof 0.000, there wasa positiveandsignificant influence betweenthe variablesWork Culture(X2) toWork Motivation(Y1) witht-count 6.258and1.985fort-table with a significance valueof 0.000, andthere wassignificant influencebetweenWork motivation variables(Y1) ofLecturerperformance(Y2) withF value of242.062andFtablesfor3.937withpvalueof 0.000. Keywords: Leadership, work culture, work motivation and lecturerperformance